Dealing with Discrepant Expectations: Response Strategies and Managerial Effectiveness - Tsui, Anne S.; Ashford, Susan J.; Clair, Lynda St.; Xin, Katherine (Academy of Management Journal, 1995)
This study examined the relationship between four strategies for managerial responses to the discrepant expectations of constituents and managerial effectiveness as perceived by superiors, subordinates, and peers. Results based on two samples including 410 managers, 452 superiors, 1,096 subordinates, and 1.071 peers consistently suggested that exerting extra effort and explaining decisions are positively associated with effectiveness perceptions. Attempts to change others' expectations and avoidance are negatively associated with effectiveness. These results support the importance of adaptive self-regulation by managers and underscore the value of responsiveness to constituents' expectations.